2022
DOI: 10.1002/er.7672
|View full text |Cite
|
Sign up to set email alerts
|

A novel collaborative multiscale weighting factor‐adaptive Kalman filtering method for the time‐varying whole‐life‐cycle state of charge estimation of lithium‐ion batteries

Abstract: Summary Accurate state of charge (SOC) estimation is essential for the whole‐life‐cycle safety guarantee and protection of lithium‐ion batteries, which is quite difficult to realize. In this study, a novel weighting factor‐adaptive Kalman filtering (WF‐AKF) method is proposed for the accurate estimation of SOC with a collaborative model for parameter identification. An improved bipartite electrical equivalent circuit (BEEC) model is constructed to describe the dynamic characteristics combined with the mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It is worth noting that the change of ambient temperature shows strong uncertainty, which is mainly caused by the complex and changeable use environment of the battery. 19 Temperature mainly affects important parameters such as battery capacity and internal impedance. 20 Specifically, related studies have shown that the capacity varies by up to 15% under different ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the change of ambient temperature shows strong uncertainty, which is mainly caused by the complex and changeable use environment of the battery. 19 Temperature mainly affects important parameters such as battery capacity and internal impedance. 20 Specifically, related studies have shown that the capacity varies by up to 15% under different ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%